Status of pediatric echocardiography clinical trials: a cross-sectional study of registered trials in ClinicalTrials.gov - Mao, Li-Juan; Wang, Lan; Lv, Dong-Mei (Frontiers in Pediatrics, 2023)
Background: Randomized clinical trials are often considered to be the highest level of evidence to support clinical decisions. The objective of this study is to determine the fundamental characteristics of pediatric echocardiography clinical trials registered in ClinicalTrials.gov. Methods: A data set including pediatric echocardiography clinical trials was downloaded from ClinicalTrials.gov until May 13, 2022. We searched the PubMed, Medline, Google Scholar, and Embase databases to extract publication data. Pediatric echocardiography trial characteristics, application areas, and publication status were described. The secondary objectives were to evaluate factors associated with trial publication. Results: We identified 410 pediatric echocardiography reporting definite age, of which 246 were interventional and 146 were observational. Drug interventions were the most commonly studied (32.9%). The most applied area of pediatric echocardiography was congenital heart disease, followed by hemodynamics of preterm or neonatal infants, cardiomyopathy, inflammatory heart disease, pulmonary hypertension, and cardio-oncology. According to the primary completion data, 54.9% of the trials were completed before August 2020. 34.2% of the trials had been published within 24 months. Union countries and quadruple masking were more likely to be published. Conclusion: Echocardiography is rapidly evolving in pediatric clinical applications, including anatomic imaging and functional imaging. Novel speckle tracking techniques have also been pivotal in the assessment of cancer therapeutics-related cardiac dysfunction. Most clinical trials in pediatric echocardiography are published in a timely fashion. Concerted efforts are needed to promote trial transparency.